Upgrading The Web-Based Credit Score Calculation System - Nanda Lidya Fadillah; Vivianti Vivianti (IPTEK The Journal for Technology and Science, 2022)
The development of the credit score system is a development that aims to streamline the time and performance of Widyaiswara at the Makassar Religious Education and Training Center. However, the previous system development did not have the Overload task verification and credit score features, so Widyaiswara needed manual input. The Abundant Task feature is a feature that allows Widyaiswara to input credit numbers above the position following the provisions for reducing credit scores following applicable regulations. Meanwhile, the credit score verification feature ensures that the credit score entered follows the specified conditions. This study aims to develop these two features for upgrading the system using the Waterfall model development. This model was chosen because it fits the needs of systematic and sequential system development. The test results show that the system has met the ISO/IEC 25010 standard; the functional feasibility is worth 1 (one), which means the system is working well. While the results of the usability test of the system are 90.4%, the system is declared very feasible to input and calculate credit scores efficiently. The result shows that the upgrading of the web-based credit score calculation system has been effectively used for inputting overflow assignments and verifying credit scores.